2020
DOI: 10.3892/ol.2020.11468
|View full text |Cite
|
Sign up to set email alerts
|

PRDX4 overexpression is associated with poor prognosis in gastric cancer

Abstract: Peroxiredoxin IV (PRDX4) is a multifunctional protein that is involved in cell protection against oxidative injury, regulation of cell proliferation, modulation of intracellular signaling, and the pathogenesis of tumors. We previously conducted a proteomic analysis to investigate tumor-specific protein expression in gastric cancer. The aim of the present study was to investigate whether PRDX4 could be a marker of poor prognosis in patients with gastric cancer. Immunohistochemistry was used to validate PRDX4 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…In relation to the data from TCGA database, the R language analysis results showed that the survival time of patients with high expressions of the PRDX4 gene was not significantly different from that of patients with low expressions of the gene (P>0.05). Conversely, Park et al ’s research findings ( 12 ) suggest that the survival time of patients with high expressions of the PRDX4 gene was significantly lower than that of patients with low expressions of the gene (P<0.05) ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In relation to the data from TCGA database, the R language analysis results showed that the survival time of patients with high expressions of the PRDX4 gene was not significantly different from that of patients with low expressions of the gene (P>0.05). Conversely, Park et al ’s research findings ( 12 ) suggest that the survival time of patients with high expressions of the PRDX4 gene was significantly lower than that of patients with low expressions of the gene (P<0.05) ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 85%
“…A P value <0.05 was considered statistically significant. Additionally, we used the survival curve of PRDX4 and gastric cancer in Park et al ’s study as an auxiliary explanation ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…They suggest PALB2 mutations predispose specifically to aggressive prostate cancers [30] . PRDX4 belongs to the typical 2-Cys PRDXs group and involved cell protection against oxidative injury, regulation of cell proliferation, modulation of intracellular signaling and the pathogenesis of tumors [31] . The PRDX4 show overexpression in many tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Since ANXA2 expression is even higher in MBC, our enhancer-promoter interaction model may provide a way to understand the mechanism by which MBC becomes resistance to standard therapy. Similarly, PRDX4 is overexpressed in several cancers such as gastric cancer 65 , lung cancer 66 , and breast cancer 54 . In addition, elevated PRDX4 expression is associated with worse overall and disease-free survival in female breast cancer patients 54 .…”
Section: Discussionmentioning
confidence: 99%